A Comparative Study of Insect Succession on Rabbit Carrion in Three Different Microhabitats. Issue 3 (11th January 2019) - Haddadi, Rania; Alajmi, Reem; Abdel-Gaber, Rewaida
Abstract: Insect succession on three rabbit carcasses placed 110.49 cm above ground in winter in Riyadh City, Saudi Arabia was examined in three different microhabitats: dry, semi-submerged, and submerged in tap water. The complete decomposition of the carcasses took 20 d and included five stages. In total 715 insects collected from carrion in different microhabitats were identified morphological, followed by the partial sequence confirmation of their 16S rRNA mitochondrial genes. Results showed that the insect species found and species richness differed among microhabitats. Carrion placed in the dry microhabitat showed the highest species richness and colonized by 400 insect specimens belonging to 16 species. Carrion placed in the semi-submerged microhabitat contained 271 insect specimens belonging to 12 species, showing a relatively low species richness. Lastly, the submerged microhabitat showed the lowest species richness, as the carrion placed in it attracted only 44 insects belonging to 9 species.